Was Copernicus an Astrologer? - George Borski; Ivan Kolkov (Studia Historiae Scientiarum)
The question ‘Was Copernicus an astrologer’ is prima facie very clear, while in fact being quite ambiguous. This question should rather be regarded as a vast topic covering lots of more concise questions such as ‘Was Copernicus thoroughly educated in astrology?’, ‘Did Copernicus believe in astrology?’ or ‘Did a mature Copernicus practice astrology?’